Mini-mental state examination-P for elderly Filipinos - Ligsay, Antonio D. (2003)
The most popular mental status examination is Folstein's Mini-Mental State Examination (MMSE). It is a comprehensive evaluation of orientation, registration, attention, calculation, recent and remote memory, comprehension, reading and writing. Because of peculiarities of the Pilipino language and the effect of ethnic background on the MMSE, the Pilipino version (MMSE-P) was developed. This is a multi-center, hospital based case control study whose objective were, to determine the validity of the Mini-Mental State Examination - Pilipino version (MMSE-P) in predicting dementia and to determine the factors affecting the performance of the test. The study was conducted from October 2001 to January 2003. There were 53 cases and 63 controls. When used alone, the best cut-off score of the MMSE-P for Filipinos in predicting dementia is 22/23 with a sensitivity of 0.85 and a specificity of 0.86. Age and family history of dementia are significantly associated with dementia and the level of education modifies the effect of the MMSE-P on dementia. A logistic regression model was derived which showed the relationship of these factors to dementia. A model probability was constructed and at cut-off 0.45, the sensitivity and specificity for detecting dementia were both 0.91. Three domains were shown to predict the presence of dementia. They are: Domain 1 (orientation to time), domain 2 (orientation to place) and domain 3 (recall). The study showed that the MMSE-P can be used to accurately screen for dementia. Further field studies are recommended to test the MMSE-P in different settings.